Avaliação do impacto de dois programas do governo brasileiro na saúde bucal de usuarios do Sistema Único de Saúde: estudo transversal de base populacional - Recchi, Andrea Fontoura (2013)
Background: The health status of a population is directly associated with the social conditions of the place where they live. Likewise, oral health is also linked to social determinants, especially the individual and family income, access to health services and social interaction. Methods: It is a cross-sectional population-based survey whose target population comprises adults above 18 years, of both sexes, users of the Brazilian Public Health System (BPHS). It aims to evaluate the impact of the Family Health Strategy (FHS) and Bolsa Familia (BF) in oral health of this population, carried in Porto Alegre, in units of the Family Health and Traditional ones. Participants answered a structured interview and had their mouth examined for investigation of oral health. The association between variables was calculated using negative binomial, using the statistical package R 3.0.1.t. Results: A sample of 187 adults was studied, which comprised 127 (68, 2%) women and 59 men (31, 7%). The mean DMFT (decayed, missed and filled teeth) increase according with age, being 1.6 for the age 18-19 years and 23.5 for older than 74 years. DMFT was equal to zero in only 12 participants (6,4%). The number of missed teeth increase with age and brushing frequency and decrease with income and flossing. The number of decayed teeth decrease with age (RR=0.98; 95% CI 0.97-0.98) and in subjects that receive the cash transfer BF (RR=0.89; 95% CI 0.79-0.98). The presence of filled teeth decreased in subjects who live in áreas covered by FHS (rr=0.74; 95% CI 0.52-0.95) area and increase according with age (RR=1.02; 95% CI 1.01-1.03) and in people with frequency of flossing less than once a day (RR=1.47, 95% CI 1.09-1.99). The presence of sound teeth decrease with age (RR 0.98, 95% CI 0.97-0.98) and in areas with FHS (RR=0.89, 95% CI 0.80-0.98). Conclusions: The oral health measured by the DMFT index and its components is associated with both, type of primary healthcare model and income (family income and Bolsa Familia access). In general, the oral health of the studied sample is better than the nationwide mean, translated in the higher number of sound teeth.